Upregulation of the angiotensin-converting enzyme 2/angiotensin-(1-7)/Mas receptor axis in the heart and the kidney of growth hormone receptor knock-out mice - Giani, Jorge Fernando (2012)
Objective: Growth hormone (GH) resistance leads to enhanced insulin sensitivity, decreased systolic blood pressure and increased lifespan. The aim of this study was to determine if there is a shift in the balance of the renin-angiotensin system (RAS) towards the ACE2/Ang-(1-7)/Mas receptor axis in the heart and the kidney of a model of GH resistance and retarded aging, the GH receptor knockout (GHR. -/-) mouse. Design: RAS components were evaluated in the heart and the kidney of GHR -/- and control mice by immunohistochemistry and Western blotting (n = 12 for both groups). Results: The immunostaining of Ang-(1-7) was increased in both the heart and the kidney of GHR. -/- mice. These changes were concomitant with an increased immunostaining of the Mas receptor and ACE2 in both tissues. The immunostaining of AT1 receptor was reduced in heart and kidney of GHR -/- mice while that of AT2 receptor was increased in the heart and unaltered in the kidney. Ang II, ACE and angiotensinogen levels remained unaltered in the heart and the kidney of GH resistant mice. These results were confirmed by Western blotting and correlated with a significant increase in the abundance of the endothelial nitric oxide synthase in both tissues. Conclusions: The shift within the RAS towards an exacerbation of the ACE2/Ang-(1-7)/Mas receptor axis observed in GHR. -/- mice could be related to a protective role in cardiac and renal function; and thus, possibly contribute to the decreased incidence of cardiovascular diseases displayed by this animal model of longevity.